2005
DOI: 10.1590/s1414-32832005000100008
|View full text |Cite
|
Sign up to set email alerts
|

Grupo de adesão ao tratamento: espaço de "ensinagem" para profissionais de saúde e pacientes

Abstract: O artigo apresenta uma prática de atenção à saúde - Grupos de Adesão ao Tratamento - que tem evidenciado um campo potencial de terapêutica, de ensino e de aprendizagem para pacientes e profissionais de saúde. Trata-se de cenário de interação de diferentes pessoas, conceitos, valores e culturas no qual cada ator se diferencia e se reconhece no outro em dinâmicas que possibilitam falar, escutar, sentir, indagar, refletir e aprender a pensar. Caracteriza-se por ser um grupo informativo, reflexivo e de suporte, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
36

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 1 publication
0
31
0
36
Order By: Relevance
“…These include the daily performance of voice exercises, a more balanced vocal production, and the elimination of abusive vocal behaviors (7) , especially in patients with behavioral dysphonia, in which these changes are essential for the maintenance of the gains at therapy. Such patient compliance or readiness for treatment may relate to various external and internal individual factors such as: age; gender; duration of therapy and need for changes in the patient's lifestyle with treatment (8) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These include the daily performance of voice exercises, a more balanced vocal production, and the elimination of abusive vocal behaviors (7) , especially in patients with behavioral dysphonia, in which these changes are essential for the maintenance of the gains at therapy. Such patient compliance or readiness for treatment may relate to various external and internal individual factors such as: age; gender; duration of therapy and need for changes in the patient's lifestyle with treatment (8) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that group work reveals itself as a place for reflections, so that each one, within its limitations and possibilities, makes (re)significations about its problems (2,8) . Therefore, group therapy gives the opportunity for patients to become more aware of their voice problems and discuss these issues post-therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations